Estimating and explaining the effect of education and income on head and neck cancer risk: INHANCE consortium pooled analysis of 31 case‐control studies from 27 countries. Issue 5 (23rd August 2014) - Conway, David I.; Brenner, Darren R.; McMahon, Alex D.; Macpherson, Lorna M.D.; Agudo, Antonio; Ahrens, Wolfgang; Bosetti, Cristina; Brenner, Hermann; Castellsague, Xavier; Chen, Chu; Curado, Maria Paula; Curioni, Otávio A.; et al.
<x xml:space="preserve">Abstract</x> Low socioeconomic status has been reported to be associated with head and neck cancer risk. However, previous studies have been too small to examine the associations by cancer subsite, age, sex, global region and calendar time and to explain the association in terms of behavioral risk factors. Individual participant data of 23, 964 cases with head and neck cancer and 31, 954 controls from 31 studies in 27 countries pooled with random effects models. Overall, low education was associated with an increased risk of head and neck cancer (OR = 2.50; 95% CI = 2.02 – 3.09). Overall one‐third of the increased risk was not explained by differences in the distribution of cigarette smoking and alcohol behaviors; and it remained elevated among never users of tobacco and nondrinkers (OR = 1.61; 95% CI = 1.13 – 2.31). More of the estimated education effect was not explained by cigarette smoking and alcohol behaviors: in women than in men, in older than younger groups, in the oropharynx than in other sites, in South/Central America than in Europe/North America and was strongest in countries with greater income inequality. Similar findings were observed for the estimated effect of low versus high household income. The lowest levels of income and educational attainment were associated with more than 2‐fold increased risk of head and neck cancer, which is not entirely explained by differences in the distributions of behavioral risk factors for these cancers and which varies across cancer sites, sexes, countries and country income inequality levels.